The impact of virtual nature therapy on stress responses: A systematic qualitative review - Abdullah, S.S.S. (MDPI, 2021)
This study aims to review the key findings of past studies that assessed the impact of virtual environments, such as nature and forests for stress therapy. Previous research has found that virtual reality (VR) experiences affect socio-affective behavior, indicating the potential of using VR for cognitive and psychological stress therapy. However, evidence for the impacts of virtual forest therapy as a stress-reduction technique is lacking, and the usefulness of these techniques has yet to be determined. This review was carried out following the preferred reporting items for meta-analyses and systematic reviews. It summarized the literature and provided evidence on virtual forest therapy (VFT) effectiveness in stress relief. We conducted a literature search considering VR-related studies published from 2013 until June 2021 for different databases, including Embase, Medline/PubMed, Hindawi, ScienceDirect, Scopus, Web of Science, Taylor & Francis, and the Cochrane Library, to see how effective VFT reduces stress levels and improves mental well-being. According to the set inclusion criteria, eighteen relevant papers detailing original research were eligible for inclusion. This overview suggests that VR provides benefits for assessing and reducing stress levels. While real natural environments effectively promote recovery from stress, virtual exposure to nature also positively affects stress. Thus, VR could be an effective technique for promoting relaxation, particularly during the COVID-19 pandemic, where stress levels rise globally. However, more in-depth studies are required to substantiate this potential field of VR relaxation. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.